Efficacy and Outcomes of Faecal Microbiota Transplantation for Recurrent Clostridioides difficile Infection in Children with Inflammatory Bowel Disease. (12th November 2021) - Nicholson, Maribeth R; Alexander, Erin; Ballal, Sonia; Davidovics, Zev; Docktor, Michael; Dole, Michael; Gisser, Jonathan M; Goyal, Alka; Hourigan, Suchitra K; Jensen, M Kyle; Kaplan, Jess L; Kellermayer, Richard; et al.
Abstract: Background: Children with inflammatory bowel disease [IBD] are disproportionally affected by recurrent Clostridioides difficile infection [rCDI]. Although faecal microbiota transplantation [FMT] has been used with good efficacy in adults with IBD, little is known about outcomes associated with FMT in paediatric IBD. Methods: We performed a retrospective review of FMT at 20 paediatric centres in the USA from March 2012 to March 2020. Children with and without IBD were compared with determined differences in the efficacy of FMT for rCDI. In addition, children with IBD with and without a successful outcome were compared with determined predictors of success. Safety data and IBD-specific outcomes were obtained. Results: A total of 396 paediatric patients, including 148 with IBD, were included. Children with IBD were no less likely to have a successful first FMT then the non-IBD affected cohort [76% vs 81%, p = 0.17]. Among children with IBD, patients were more likely to have a successful FMT if they received FMT with fresh stool [ p = 0.03], were without diarrhoea prior to FMT [ p = 0.03], or had a shorter time from rCDI diagnosis until FMT [ p = 0.04]. Children with a failed FMT were more likely to have clinically active IBD post-FMT [ p = 0.002] and 19 [13%] patients had an IBD-related hospitalisation in the 3-month follow-up. Conclusions: Based on the findings from this large US multicentre cohort, the efficacy of FMT for the treatment of rCDI did not differ in children with IBD. Failed FMT among children with IBD was possibly related to the presence of clinically active IBD.